1994
DOI: 10.1063/1.112485
|View full text |Cite
|
Sign up to set email alerts
|

Counter-oxidation of superficial Si in single-crystalline Si on SiO2 structure

Abstract: Articles you may be interested inLuminescence of phosphorus containing oxide materials: Crystalline SiO 2 P and 3 P 2 O 5 7 SiO 2 ; CaO P 2 O 5 ; SrO P 2 O 5 glasses AIP Conf.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 9 publications
1
30
0
Order By: Relevance
“…Furthermore, recent work has shown that some oxygen diffuses through the silicon layer to the interface with the buried oxide, enough to grow a few nanometers of SiO 2 at this interface. 31 This ensures that both the upper and lower interfaces of the silicon layer have equivalent passivation. Typical Si layers were tapered 10 nm over 50 mm.…”
Section: Sample Preparationmentioning
confidence: 99%
“…Furthermore, recent work has shown that some oxygen diffuses through the silicon layer to the interface with the buried oxide, enough to grow a few nanometers of SiO 2 at this interface. 31 This ensures that both the upper and lower interfaces of the silicon layer have equivalent passivation. Typical Si layers were tapered 10 nm over 50 mm.…”
Section: Sample Preparationmentioning
confidence: 99%
“…22,23 However, the thickness increase of buried dielectrics in INTS is not more than 1 nm under the typical condition, because nitrided layers ͑at both surface and interface͒ act as a diffusion barrier against reactants. This is, of course, preferable for the formation of thin gate oxynitrides in the MOS ultralarge scale integrated ͑ULSI͒ technology.…”
Section: Resultsmentioning
confidence: 98%
“…ecsdl.org/site/terms_use address. Redistribution subject to ECS terms of use (see 157.182.150 22. Downloaded on 2015-06-29 to IP…”
mentioning
confidence: 98%
“…The PIA was carried out at 1325-1350°C in Arϩ0.5% O 2 for 5 or 6 h. Following the PIA, oxygen was introduced into the BOX of some structures by a supplemental ion implantation ͑doses 1ϫ10 17 and 5ϫ10 17 cm Ϫ2 ͒ and followed by a PIA in Ar at 1000°C for 1 h. Some of the low-dose structures were subjected to an internal thermal oxidation ͑ITOX͒ at 1250-1350°C in Ar with 10% or 30 % of O 2 for 4 or 6 h. During this process, the BOX grows as a result of oxygen transport through the top silicon layer. 68 For the sake of comparison, also studied were oxide layers produced by implanting Si with such high oxygen dose (Ͼ10 19 cm Ϫ2 ) that the entire top Si layer is consumed ͑equilibrium oxide͒. 69 The equilibrium oxides received the same PIA as the conventional SI-MOX structures, however, without the top Si layer, i.e., in an unconfined configuration.…”
Section: Methodsmentioning
confidence: 99%